2019
DOI: 10.1002/hbm.24742
|View full text |Cite
|
Sign up to set email alerts
|

When I relive a positive me: Vivid autobiographical memories facilitate autonoetic brain activation and enhance mood

Abstract: Autobiographical memory is vital for our well‐being and therefore used in therapeutic interventions. However, not much is known about the (neural) processes by which reliving memories can have beneficial effects. This study investigates what brain activation patterns and memory characteristics facilitate the effectiveness of reliving positive autobiographical memories for mood and sense of self. Particularly, the role of vividness and autonoetic consciousness is studied. Participants (N = 47) with a wide range… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 77 publications
1
12
0
Order By: Relevance
“…The fusiform cortex has been linked to processing of object details (Donix et al, 2010). A significant interaction between remoteness and rehearsal confirmed that rehearsal (i.e., repetition) was greatest for remote compared to recent memories, in particular in the fusiform cortex, lateral temporal cortex and insula, which has a role in subjective experience of emotional AMs (Van Schie et al, 2019).…”
Section: Discussionmentioning
confidence: 90%
“…The fusiform cortex has been linked to processing of object details (Donix et al, 2010). A significant interaction between remoteness and rehearsal confirmed that rehearsal (i.e., repetition) was greatest for remote compared to recent memories, in particular in the fusiform cortex, lateral temporal cortex and insula, which has a role in subjective experience of emotional AMs (Van Schie et al, 2019).…”
Section: Discussionmentioning
confidence: 90%
“…While her various symptoms, such as fear, guilt, and nihilism, may be intertwined in such delusional belief, the theme of death may emphasize nihilistic aspects of her symptoms. Although further research is needed to fully understand the impact of interoceptive dysfunction on memory, the insular cortex has been reported as being associated with the vividness and richness of autobiographical memory 21,22 . Thus, an affected recall could serve as the first factor in the development of such symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…The 'Reliving Autobiographical Memories' (RAM) task has previously been described in Van Schie, et al (2019b).…”
Section: Reliving Autobiographical Memories Taskmentioning
confidence: 99%
“…Vividness seems crucial for positive memories to have an emotional benefit (Engelhard, van Uijen, & van den Hout, 2010;Van Schie, Chiu, Heiser, Rombouts, & Elzinga, 2019b). Memories that are relived less vividly are not re-experienced with the same emotional intensity as vivid memories (Philippe, et al, 2009;Van Schie, et al, 2019b). The vivid reliving of memories can be achieved by higher autonoetic consciousness (i.e.…”
Section: Introductionmentioning
confidence: 99%